Problematika Sosial - Moral Generasi Muda di Era Digital: Tinjauan Teologis Pendidikan Agama Kristen - Koen, Rahel Febriyanti; Rangga, Oktavianus (JURNAL KADESI, 2026)
The development of digital technology has changed the lifestyles of the younger generation, not only in communication and access to information, but also in the formation of character, identity, and spirituality. Behind this convenience, various socio-moral problems have emerged such as social anxiety, identity crises, online bullying, hedonistic lifestyles, gadget addiction, promiscuity, and weakened spiritual discipline, which indicate a gap between Christian faith values ??and the life practices of the younger generation in the digital era. This study aims to analyze the forms of socio-moral problems faced by the younger generation, identify the causal factors, and formulate theological responses from the perspective of Christian Religious Education. The study uses a qualitative method with a library approach through analysis of the Bible, theological literature, and related scientific studies. The novelty of this study lies in its integrative and holistic approach that links digital social phenomena with comprehensive theological reflections on Christian Religious Education, while also offering a contextual, dialogical, and transformative model of faith formation to shape a young generation that is spiritually mature, morally integrated, and responsible in the digital space. With a holistic approach encompassing the cognitive, affective, and behavioral dimensions of Christian Education, it is hoped that it will shape a younger generation that is not only digitally proficient, but also spiritually mature, morally upright, and capable of providing a tangible Christian witness amidst the dynamics of a digital society.